Employee privacy violations and their consequences - Aldana Bakhit Alnaimi (Zien Journals, 2023)
The subject of the study is important because it represents the worker as the cornerstone of the production process in various fields and fields, and because of this status that he enjoys, research in the guarantees and rights that must be enjoyed by a very important research requirement, the study is based on the assertion of violations to which the worker is exposed in his privacy and the consequent effects. As the analytical and comparative technique was used to solve this topic, the primary question is what are the violations to which the worker is exposed in his privacy and their consequences? The study was divided into two sections to accomplish its goals. The first dealt with compensation through contractual liability, through which the type of worker's injury, the scope and limits of compensation, the extent of its mandatory requirements, and the availability of elements of work injury and their requirements were discussed. Then we went on to the second section, which was about compensation through missive responsibility, where we talked about the pictures of the worker being assaulted before the contract was signed and the Qatari legislator's opinion on these violations. The researcher ultimately came to a number of conclusions, the most significant of which was that the harm may affect both the physical and moral entity of the person, meaning that the worker's injury may be material or moral or both. The researcher also came to a number of recommendations, the most significant of which was the amendment of the Labor Law by stipulating the images of violations of rights and freedoms in detail and singling them out with a separate chapter so that the employer is not arbitrarily in that
Keywords: Labor law; employee; privacy violation